Toxicological assessment of citral and geraniol: Efflux pump inhibition in Staphylococcus aureus and invertebrate toxicity - Gildênia Alves de Araújo; Cícera Datiane de Morais Oliveira Tintino; Raimundo Luíz Silva Pereira; Isaac Moura Araújo; Cícera Laura Roque Paulo; João Arthur de Oliveira Borges; Ewerton Yago de Sousa Rodrigues; Ângella Eduarda da Silva; Francisco Assis Bezerra da Cunha; Zildene de Sousa Silveira; Nair Silva Macedo; Henrique Douglas Melo Coutinho; et al. (Toxicology Reports)
This study aimed to evaluate the antibacterial activity against multi-drug-resistant strains carrying efflux pumps and assess their toxicity on Drosophila melanogaster and Aedes aegypti models. Microdilution tests in broth were performed to determine the Minimum Inhibitory Concentration (MIC). The efflux pump inhibition was evaluated by analyzing the reduction in antibiotic MIC and Ethidium Bromide (EtBr) MIC when combined with the products. Mortality assay and negative geotaxis were conducted on D. melanogaster specimens, and insecticidal activity assays were performed on A. aegypti larvae. Only geraniol reduced the antibiotic MIC when combined, reducing from 64 µg/mL to 16 µg/mL in the 1199B strain of S. aureus. When combined with EtBr, both geraniol and citral reduced EtBr MIC, with geraniol decreasing from 64 µg/mL to 16 µg/mL and citral decreasing from 64 µg/mL to 32 µg/mL. Regarding the S. aureus K2068 strain, geraniol reduced the antibiotic MIC from 16 µg/mL to 8 µg/mL, and citral reduced it from 16 µg/mL to 4 µg/mL. In combination with EtBr, all monoterpenes reduced MIC from 64 µg/mL to 32 µg/mL. Both products exhibited toxicity in D. melanogaster; however, citral showed higher toxicity with a precisely determined LC50 of 2.478 μL. As for the insecticidal action on A. aegypti, both products demonstrated toxicity with cumulative effects and dose-dependent mortality.